LOCAL KNOWLEDGE OF FLOOD PREPAREDNESS: CURRENT PHENOMENA TO FUTURE ACTION (Jurnal Teknologi (Sciences & Engineering), 2016)
Understanding local knowledge towards isolated incidents is important as a means to the inclusion and participation of local people in disaster management and preparedness activities. Indeed, investigating how local people or communities in a particular area view and interact with their environment and its changes is crucial. In recent years, extreme weather phenomenon has caused havoc not only other parts of the world, but also in Malaysiawith major destructions to most lives and properties. Much research and development has focused on these global phenomena. The situation is getting alarming in Malaysia, especially along the eastern coastal area. In light of the big flood of Kelantan in 2014, this study aimed to discover the local communities’ knowledge on flood preparedness. Face-to-face interviews and a series of workshops were conducted with 15 respondents, from professionals, voluntaries, community leaders, and affected communities. The aftermath of the big flood showed that all forms of transportation were affected, lives, farm lands and properties were lost, and economic activities were grounded. Worst of all, these disasters are reported to be linked to human actions as the key cause. Thus, it is recommended that more efforts be taken to channel the information on flood preparedness from the affected communities, for future use. Besides, well-established and clear guidelines will help other relevant players like NGO, voluntaries, helpers, officers, and communities to play their roles in the most efficient way to face any disaster.